Absenteísmo de técnicos de enfermagem em uma unidade de urgência e emergência de um hospital universitário - Renata Bastos Peres (2016)
This study sought to understand the situations of life and daily work that influence the absenteeism of nursing technicians of the emergency care sector of a University Hospital at Belo Horizonte. A single case study of qualitative approach, whose subjects were nursing technicians who work in Emergency Care sector was carried out. Data were collected in March and April 2015 through interviews with semi-structured and technical visit at the institution and submitted to content analysis. Emerging from the results four categories: (1) Daily work in an emergency care sector; (2) relationship of professionals with work on the urgency and the hospital, divided into two subcategories: (2.1) Identification with the work on urgency, (2.2) Factors that generate satisfaction or dissatisfaction; (3) Reasons self-reported of absenteeism a view of reality; (4) Effects of absenteeism in the workplace and for professionals. The results show a dynamic service every day, agitated and unpredictable. The reports show identification of technicians with the emergency department and suitability of the professional profile of the work done, with sector characteristics and patients. With regard to situations of satisfaction and job dissatisfaction, were identified as reasons of satisfaction, to work with critically ill patients and obtain good recovery thereof, which gives success in attendance, and good relationship with the team. As reasons for dissatisfaction were evidenced feelings resulting from devaluation of the low financial recognition, work overload, patients and uncooperative companions and, contradictorily, impaired interpersonal relationship with the team. The results show that health issues are not the only reasons for absenteeism, as reports emerged of family problems of interference as troubled love relationships, need for care of the children, transport, protests in the city, staff turnover, professional stress, interpersonal problems with leadership, death of family members, exposure risks to infectious contagious disease, parties and judicial appointments. It was possible to identify a permanent relationship of personal life and work reflected in absenteeism. As for absenteeism impact on the daily work showed up the burden faced by workers present, the disorganization of the labor and sector process, compromising the quality of care and the damage to the guilty employee who is subjected to punitive actions, even if is pay off only. The results of this research, can subsidize discussions about absenteeism in the institution aiming management policies that contribute to their reduction and consequent improvement to the user, employee and manager.